(untitled) (Journal of Hama University, 2024)
The rapid growth in knowledge and technology poses a great challenge to individuals، which makes it necessary for them to possess skills that help them to compete and lead، and thus the ability to survive and succeed. The current research aimed to study the relationship between soft management skills and entrepreneurial orientation of students of the College of Nursing. According to the descriptive analytical method، the data were collected using a questionnaire consisting of three parts from an available quota sample that included (300) male and female students from the Faculty of Nursing at Tishreen University، after analyzing the data using the SPSS program. The most important results were: Students’ possession of an above-average level of soft management skills (3.43 ± 0.66)، first of which is leadership skill، then communication and teamwork skill; The students’ entrepreneurial orientation were within the above-average level (3.38 ± 0.25)، starting with initiative and then taking risks. With a strong positive correlation between all aspects of soft management skills and entrepreneurial orientation، and there are differences in soft skills due to the gender variable in favor of females. The study recommends the need to include soft skills and entrepreneurship concepts within university curricula and to provide the infrastructure that supports entrepreneurship and creativity among university students